Taming Two Waves of the Covid-19 Pandemic: The Case of Indonesia - Haryono, Endi; Yunia Harsari, Ayu (KnE Social Sciences, 2022)
On 6 October 2021, the Nikkei Covid-19 Recovery Index ranked Indonesia as 54 out of 120 countries in the world. This placed Indonesia as the best ASEAN country in its response to the Covid-19 pandemic; this was compared to Malaysia which was ranked 102, Singapore at 70, and Thailand at 109. The Indonesian policy for the Covid-19 pandemic in principle consisted of two policies of guided lockdown: PSBB (in January 2021 when confronting the first wave of the pandemic) and PPKM (in July 2021 when confronting the second wave). The Covid-19 pandemic unveiled two concerning problems of national development in Indonesia: intra-ministry coordination and public communication. The success of the Government of Indonesia’s policy to respond to the Covid-19 pandemic was mostly due to the determination of the Government directed by President Joko Widodo. On the other hand, as a consequence of these policies, the national development plan of Indonesia to realize the vision of ‘Indonesia Maju’ was disrupted. This success of addressing the problems of intra-ministry coordination and communication contributed to an important achievement for Indonesia. Keywords: PSBB, PPKM, Indonesian policy, intra-ministry coordination, public communication